2020
DOI: 10.1111/acem.14114
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Clinical Seizure Characteristics on Recognition and Treatment of New‐onset Focal Epilepsy in Emergency Departments

Abstract: Objective Many people with new‐onset focal epilepsy initially seek evaluation in emergency departments (EDs), and treatment decisions in EDs can influence likelihood of seizure recurrence. Using data collected for the Human Epilepsy Project (HEP), we assessed the effect of clinical seizure characteristics on ED clinical management. Methods There were 447 participants with new‐onset focal epilepsy seen within 4 months of treatment initiation who were eligible and enrolled in HEP. Seizure calendars and medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…After assessment of full-text papers, we found 15 papers that met the criteria for inclusion, plus an additional two earlier papers from our own library (see Tables S1 and S2). [2][3][4][15][16][17][18][19][20][21][22][23][24][25][26][27][28] One paper was a registry study that used International Classification of Diseases (ICD) codes to identify patients and included individuals who obtained antiepileptic drugs (AEDs) before the epilepsy diagnosis was coded. 23 This study was included, as it met our criteria, and the numbers of treated and nontreated patients were noted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After assessment of full-text papers, we found 15 papers that met the criteria for inclusion, plus an additional two earlier papers from our own library (see Tables S1 and S2). [2][3][4][15][16][17][18][19][20][21][22][23][24][25][26][27][28] One paper was a registry study that used International Classification of Diseases (ICD) codes to identify patients and included individuals who obtained antiepileptic drugs (AEDs) before the epilepsy diagnosis was coded. 23 This study was included, as it met our criteria, and the numbers of treated and nontreated patients were noted.…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, a review of abstracts resulted in 54 potentially eligible studies. After assessment of full‐text papers, we found 15 papers that met the criteria for inclusion, plus an additional two earlier papers from our own library (see Tables and ) 2–4,15–28 . One paper was a registry study that used International Classification of Diseases (ICD) codes to identify patients and included individuals who obtained antiepileptic drugs (AEDs) before the epilepsy diagnosis was coded 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Pellinen et al examined the role of the latter through an analysis of the outcomes of emergency department (ED) visits in the same multicenter cohort of newly diagnosed focal epilepsy. 8 They found that the majority of those with nonmotor seizures presented to an ED after their first motor seizure, but that in those with prior nonmotor seizures, that history was elicited by the ED physician in only one-fifth of cases.…”
Section: Commentarymentioning
confidence: 99%
“…Patients in whom no underlying reason for a first lifetime seizure is found may have had an isolated event or may develop recurring seizures and a diagnosis of epilepsy. The observational study by Pellinen et al 1 published in this issue of Academic Emergency Medicine serves to teach us about this latter cohort of patients using a database of those subsequently diagnosed with focal epilepsy after an initial ED visit.…”
mentioning
confidence: 99%
“…Pellinen et al 1 use a registry of patients with newly diagnosed focal epilepsy to describe the characteristics of a subset who presented to an ED shortly prior to their diagnosis. The authors note that the first onset of epilepsy was nonmotor focal seizures in slightly more than half of the patients in the ED subset, but that they rarely came to the ED for these types of seizures.…”
mentioning
confidence: 99%